Origin of Analytical Breeding of Winter Wheat (Triticum aestivum L.) in the Tsar’s Russia, and in Ukraine in particular (End of XIX– Beginning of XX centuries) - Х. М. Піпан (Plant Varieties Studying and Protection)
This article discusses the main factors of origin and development of analytical selection of winter wheat in Ukraine in late XIX - early XX century .. In particular highlight the role of scientific works of Charles Darwin, W. Rimpau, AL Sempolovskуу, IS Korzhinskуу and research institutions to increase attention to the study of local varieties of winter wheat and their improvement. Especially analyze values of Russia's first benefit from the breeding "Guide to Seed for the Advancement of cultivated plants", in which the author proposes methods for improving and creating new varieties. Since the end of XIX century selection were mainly involved in private owners on their own initiative, already in the beginning of XX century this trend more interested in the agricultural society, local and state authorities. Thanks to their support in the country organized congresses, meetings and conferences, set up research and field stations. It was during this period of transition took place in the national selection analysis.